2021
DOI: 10.3390/ijms22158030
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Responses in Oncology: Causes and Significance

Abstract: Specific anti-tumor immune responses have proven to be pivotal in shaping tumorigenesis and tumor progression in solid cancers. These responses can also be of an autoimmune nature, and autoantibodies can sometimes be present even before the onset of clinically overt disease. Autoantibodies can be generated due to mutated gene products, aberrant expression and post-transcriptional modification of proteins, a pro-immunogenic milieu, anti-cancer treatments, cross-reactivity of tumor-specific lymphocytes, epitope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 120 publications
(178 reference statements)
1
12
0
Order By: Relevance
“…It has been suggested that some MHC molecules can present viral peptides with epitopes very similar to their own peptides, which may lead to the activation of autoreactive T cells. Variations in the MHC locus are also closely related to many different autoimmune diseases (7,45,46) given dysregulation, identification of AABs in COVID-19 and its associated pathologies, as we have observed in our results, have also been demonstrated in other studies about the diversity (47), frequency and suggested function of these AABs (48).…”
Section: Discussionsupporting
confidence: 87%
“…It has been suggested that some MHC molecules can present viral peptides with epitopes very similar to their own peptides, which may lead to the activation of autoreactive T cells. Variations in the MHC locus are also closely related to many different autoimmune diseases (7,45,46) given dysregulation, identification of AABs in COVID-19 and its associated pathologies, as we have observed in our results, have also been demonstrated in other studies about the diversity (47), frequency and suggested function of these AABs (48).…”
Section: Discussionsupporting
confidence: 87%
“…When the tumor is simultaneously treated by checkpoint inhibitors, the treatment might function as a boosting agent to upkeep this T cell reaction resulting in a synergistic outcome. As the goal of ICI is to activate the immune system to fight cancer, logically, the administration of ICI has been shown to cause some autoimmune reactions, manifesting usually as mild adverse events [ 36 ]. However, this phenomenon can be thought as potentially beneficial in our treatment setup.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although the binding affinity of TCR to the self-peptides-MHC complexes has been reported to be much lower than to foreign antigens [ 60 ], the release of self-antigens in high concentrations may activate a high-dose/low-affinity response. This could compromise the peripheral tolerance, triggering autoimmune events [ 61 ].…”
Section: T Cell Response To Different Type Of Tumoural Antigensmentioning
confidence: 99%